IMPLEMENTASI BANTUAN HUKUM YANG DIBERIKAN OLEH KOMISI PERLINDUNGAN ANAK INDONESIA TERHADAP ANAK KORBAN KEKERASAN SEKSUAL - Milenia, Angelica Christin; Adhari, Ade (Universitas Ekasakti, 2023)
Sexual violence against children is a crime act that should be taken care of by the state. This crime is increasing day by day and ironically the perpetrators of this violence are the people closest to the victim such as friends, teachers or even family members. This can cause trauma for the child victim. According to Article 76 of Constitution Number 35 of 2014 regarding Child Protection, KPAI is a state institution that has the duty and authority to provide protection for children. This research is based on empirical juridical research with qualitative methods which are analyzed using inductive analysis techniques by examining the contribution of legal assistance provided by KPAI in accordance with Constitution Number 35 of 2014 regarding Amendments to Constitution Number 23 of 2002 regarding Child Protection.